INFORMATION TRANSPARENCY AND REGULATORY FOCUS TO INCREASE BUYING INTEREST IN THE INTEGRATED FOOTWEAR MARKETPLACE (IFM) - Kodrat, David Sukardi; Krisprimandoyo, Denpharanto Agung; Tambunan, Damelina Basauli (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to examine information transparency and regulatory focus to increase buying interest at the Integrated Footwear Marketplace. The informants used in this research came from consumers, suppliers, producers, funding institutions and logistics services. The research method used is descriptive qualitative. The results of this research show that the Integrated Footwear Marketplace uses two main concepts, namely co-design and economic sharing. The concept of co designing is seen in the consumer engagement menu where consumers can enter design ideas and designs and other consumers can provide responses and comments on these design ideas and designs. Transparency by showing data related to individual profiles, company profiles and various product descriptions. Information quality is related to information that is trustworthy, reliable, available on time, relevant and easy to understand. The concept of self-regulation creates natural motivation to achieve desired results. The concept of self-regulation can be grouped into approach and avoidance. This avoidance concept can be seen from the product description which explains it completely and in detail so that it can be taken into consideration regarding things that have the potential to become risks.